Directed Discovery of Tetrapeptide Emulsifiers - Scott, Gary G.; Börner, Tim; Leser, Martin E.; Wooster, Tim J.; Tuttle, Tell (Frontiers in Chemistry, 2022)
Oil in water emulsions are an important class of soft material that are used in the food, cosmetic and biomedical industries. These materials are formed through the use of emulsifiers that are able to stabilize oil droplets in water. Historically emulsifiers have been developed from lipids or from large biomolecules such as proteins. However, the ability to use short peptides, which have favorable degradability and toxicity profiles is seen as an attractive alternative. In this work, we demonstrate that it is possible to design emulsifiers from short (tetra) peptides that have tunability (i.e., the surface activity of the emulsion can be tuned according to the peptide primary sequence). This design process is achieved by applying coarse grain molecular dynamics simulation to consecutively reduce the molecular search space from the 83,521 candidates initially considered in the screen to four top ranking candidates that were then studied experimentally. The results of the experimental study correspond well to the predicted results from the computational screening verifying the potential of this screening methodology to be applied to a range of different molecular systems.